1995
DOI: 10.1113/jphysiol.1995.sp020539
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Na(+)‐Ca2+ exchanger in the rate‐dependent increase in contraction in guinea‐pig ventricular myocytes.

Abstract: 1. The intracellular sodium activity (aN^), contraction and membrane current were recorded simultaneously in voltage-clamped guinea-pig ventricular myocytes. 2. Increasing the frequency (from 0 5 to 3 Hz) of voltage clamp pulses to 0 mV from a holding potential of -80 mV led to an increase in both a'a and contraction. The ratedependent increase in contraction was reduced by 25 ,UM tetrodotoxin (TTX) and abolished with a holding potential of -40 mV. There was no rate-dependent rise in a'Na with a holding potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Faster pacing also increases diastolic calcium. The rise in calcium at high rates depends primarily on the corresponding accumulation of sodium, due to the activity of I NCX 26 . Another mechanism that promotes calcium loading at high rates is that the action potential waveform spends more time per period at plateau potentials, and so the time spent in the calcium efflux mode is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Faster pacing also increases diastolic calcium. The rise in calcium at high rates depends primarily on the corresponding accumulation of sodium, due to the activity of I NCX 26 . Another mechanism that promotes calcium loading at high rates is that the action potential waveform spends more time per period at plateau potentials, and so the time spent in the calcium efflux mode is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…If the slow shortening of the action potential is not due to changes of extracellular potassium then a likely alternative is that changes of intracellular ions, particularly sodium and calcium, are involved. Work in many cardiac tissues has shown that increasing the frequency of stimulation increases the intracellular sodium concentration, [Na + ] i (Kaila & Vaughan‐Jones, 1985; Boyett et al 1987; Harrison et al 1992; Harrison & Boyett, 1995). This increase of [Na + ] i will (via NCX) increase intracellular calcium concentration ([Ca 2+ ] i ), and we must therefore consider effects mediated by changes of both [Ca 2+ ] i and [Na + ] i .…”
Section: The Mechanism Of the Slow Changes Of Apdmentioning
confidence: 99%
“…Simulations (Faber & Rudy, 2000) suggest that this increased outward NCX current contributes to the shortening of the APD, although to the best of our knowledge there have been no experimental tests of this. One study has shown that increased stimulation of guinea‐pig ventricular myocytes results in increased outward NCX current accompanied by an increase of [Na + ] i (Harrison & Boyett, 1995). That study speculated that this current could contribute to the slow changes of APD, but no measurements of action potentials were made to demonstrate causality.…”
mentioning
confidence: 99%
“…(1993). The same mechanism appears to be involved in part in the rate‐dependent increase in contraction (Harrison & Boyett 1995). This mechanism is based on the model of Harrison et al .…”
mentioning
confidence: 97%